Aplikasi Pengarsipan Surat di Kantor Koperasi TKBM Pelabuhan Laut Nabire Berbasis Web - Cici Kamalia; Hemaf Imelda Edowai; Ester Ayuk Pusvita (Jurnal Teknologi dan Informatika, 2024)
Web-Based Application for Archiving Letters at the Nabire Sea Port TKBM Cooperative Office is an information technology solution designed to assist in the management and archiving of correspondence in the Nabire Sea Port TKBM Cooperative office environment. By using a web-based approach, this application aims to increase efficiency, speed and accuracy in the process of archiving and searching for letters, as well as allowing easy access from various locations. This application is equipped with important features such as search for letters based on certain criteria, electronic storage of letters with grouping by category and date, as well as the ability to delete, update and access mail archives easily. In addition, this application can also provide notifications for new incoming mail and provide user activity history for auditing and monitoring purposes. With the adoption of web-based technology, employees of the Nabire Sea Port TKBM Cooperative office can access this system via various devices, including desktop computers, laptops and mobile devices, providing flexibility in use. The implementation of this application is expected to increase office productivity, reduce errors in filing, and optimize overall correspondence management.